Nitrogen/nitrogen-zirconium doped cobalt nanoferrites for the catalytic degradation of 4-chlorophenol from wastewater - Kavitha Sreedharan; Manju Kurian (Next Materials, 2025)
Degradative oxidation of 4-chlorophenol in water under ambient conditions was studied by means of peroxide oxidation over nitrogen/nitrogen-zirconium doped spinel cobalt ferrite nanoparticles synthesized by wet impregnation/coprecipitation methods. X-ray diffraction, X-ray Fluorescence spectroscopy, Transmission Electron Microscopy, Fourier Transform Infra-Red spectroscopy, surface area measurements, and Energy-dispersive X-ray spectroscopic studies were done to evaluate the physicochemical properties. Single phasic cubic spinel ferrites with particle sizes ranging from 15 to 24 nm were obtained. Saturation magnetization decreased with doping of Zr and N. Zr/N doped cobalt ferrites were excellent magnetically recoverable catalysts for the abatement of 4-chlorophenol at 50 °C in 75 min, with concomitant decrease in COD levels of the residual water. The catalysts were active for four consecutive cycles without any deterioration in the spinel structure.